Caesarius of Arles : life, testament, letters - Césaire d'Arles, svatý, asi 470-542 (Translated texts for historians ;, 1994)
Caesarius was born in 469/70 and served as Bishop of Arles from 502 until his death in 542. Originally trained as a monk at Lérins, he devoted himself as Bishop to an ambitious programme of church reform and Christianization inspired by strict monastic standards of piety. Best known as a preacher, with a corpus of over 250 sermons, Caesarius also founded a monastery whose rule he composed and presided over several important church councils whose canons still survive. The documents included in this volume – most never before translated into English – vividly illustrate Caesarius’s career and the social and religious history of Provence at a time of far-reaching political change, during which the region was ruled by a series of Visigothic, Burgundian, Ostrogothic and, ultimately, Frankish kings.